Identification of tensile behaviour of polylactic acid parts manufactured by fused deposition modelling under heat-treated conditions using nonlinear autoregressive with exogenous and transfer function models - Karabeyoglu, Sencer Sureyya; Eksi, Olcay; Istif, Ilyas; Feratoglu, Kamil (WALTER DE GRUYTER GMBH, 2022)
In this study, three-dimensional (3D) printed polylactic acid (PLA) samples are annealed at slightly above the glass transition temperature to enhance the mechanical properties. Tensile and Izod impact tests are conducted to investigate the mechanical properties of 3D printed PLA specimens. Influence of different infill patterns on tensile strength and impact resistance are also observed. Porous structure of 3D printed PLA specimens is examined and average void area densities are determined via scanning electron microscope (SEM) images. Influence of void area density on mechanical properties is investigated. Tensile behaviour of 3D printed PLA parts is simulated with proposed nonlinear autoregressive with exogenous and transfer function models. While stress data and determined void area densities are used as inputs, strain data obtained from tensile tests used as output for the model structures.
Keywords: fused deposition modelling; identification; mechanical characterization; modelling; polylactic acid; MECHANICAL-PROPERTIES; TRIBOLOGICAL BEHAVIOR; OPTIMIZATION; COMPOSITES; PREDICTION; PARAMETERS; PROPERTY; ABS; PLA; Polymer Science